An empirical study on the relationship between the working capital policies and corporate performance : the case of the Portuguese Footwear Sector - Carvalho, Adriana da Costa (2020)
In the sphere of short-term decision-making, the decisions towards working capital hold a critical position. This study aims to understand if the decisions regarding the working capital policies have an impact on the profitability of firms in the Portuguese Footwear sector. To do so, annual financial data of 737 non-listed firms in the sector was collected, during a range of 10 consecutive years (2007-2016). The results of the OLS estimations for the first model revealed both a positive relationship between the degree of aggressiveness of working capital asset investment policies and corporate profitability, and a negative relationship between the degree of aggressiveness of working capital financing policies and corporate profitability. Notwithstanding, through the estimation of the second model, the overall results of the study demonstrated that, if firms in this sector increase the aggressiveness of their working capital management policy, or strategy, namely by reducing the level of working capital to the minimum amount required to run the business, those are likely to obtain lower levels of profitability.